MGS Cluster School: expanding expertise - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
14 Nov 2009. The last phase of Methodist Girls School Cluster School programme, which consists of two short courses namely, Professional Development for Teachers and English Communication, took place for 8 hours.